Integration of Pesantren Curriculum and Higher Education - Basori, Adib Rofiuddin; Nugraha, Mulyawan Safwandy; Sopidi, Sopidi; Syibromilisi, Syibromilisi (Ahlussunnah: Journal of Islamic Education, 2025)
This study analyzes the amalgamation of the pesantren curriculum and secondary education at STIT Buntet Pesantren Cirebon, focusing on Islamic tenets and academic criteria within the framework of modern education. This study aims to elucidate the implementation of the integration of the pesantren and higher curriculum at STIT Buntet Pesantren Cirebon, as well as to identify the elements that facilitate and impede its achievement. Employing a qualitative case study methodology, data are collected via participant observation, in-depth interviews, and document analysis from the Chairperson, Vice Chairperson, Head of Study Program, and students. This study explains that the integration process centers on three fundamental pillars: faith, knowledge, and charity, with a strong emphasis on moderation (wasathiyah) in the curriculum. Although integration has been successful, the problem lies in the use of pesantren values as indicators in academic evaluation, and character development in the classroom takes time. This study emphasizes the importance of optimizing the implementation of an integrative curriculum, contributing to the literature by demonstrating the application of Islamic principles in the context of practical and academic education.